2015
DOI: 10.1007/s11368-015-1172-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological soil disinfestation and water regime on suppressing Artemisia selengensis root rot pathogens

Abstract: Purpose Biological soil disinfestation (BSD) is an effective non-chemical method to control soil-borne disease by incorporating organic amendments into soil under flooding conditions. For suppressing Artemisia selengensis root rot pathogens (Fusarium oxysporum f. sp. cubense (FOC), Phytophthora spp., and Pythium spp.), the effects of BSD treatment using maize straw as organic material and water regime were investigated by greenhouse experiments. Materials and methods Pathogens infested soil was filled in green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…However, after RSD treatments, the relative abundances of organic acid producers increased, particularly in the AL groups, potentially because many Firmicutes are anaerobic bacteria and the low C/N ratio is more conducive to the formation of an anaerobic environment (Liu et al, 2016). In addition, the higher addition of substrate was related to higher relative abundance of organic acid producers, similar to the results of a study by Wen (2015). Once pathogens are inhibited, toxic organic acids are degraded during the drying process of the soil due to destruction of the anaerobic environment, thereby preventing toxicity during crop cultivation.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, after RSD treatments, the relative abundances of organic acid producers increased, particularly in the AL groups, potentially because many Firmicutes are anaerobic bacteria and the low C/N ratio is more conducive to the formation of an anaerobic environment (Liu et al, 2016). In addition, the higher addition of substrate was related to higher relative abundance of organic acid producers, similar to the results of a study by Wen (2015). Once pathogens are inhibited, toxic organic acids are degraded during the drying process of the soil due to destruction of the anaerobic environment, thereby preventing toxicity during crop cultivation.…”
Section: Discussionsupporting
confidence: 84%
“…There were two possible reasons for this result. First, Flavisolibacter is an aerobic bacterium (Kim et al, 2018); greater substrate addition would result in more favorable formation of an anaerobic environment (Wen et al, 2015), and therefore, a high addition amount was not conducive to the growth of Flavisolibacter. Second, during the early stage of cultivation, residual oxygen in the soil and dissolved oxygen in the water could provide conditions for the survival of Flavisolibacter; Flavisolibacter increased rapidly in the presence of a sufficient carbon source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we found that consecutive monoculture of P. heterophylla led to a significant increase in the relative abundance of F. oxysporum but a decrease in the potential beneficial bacteria including Burkholderia and Clostridium (Mowlick et al, 2012; Ho et al, 2015; Wen et al, 2016). Our previous studies by culture-dependent and culture-independent analysis demonstrated that F. oxysporum and other Fusarium spp.…”
Section: Discussionmentioning
confidence: 86%